Analisis Pemberian Vaksinasi Covid-19 Pada Lansia Di Wilayah Kerja Puskesmas Sematang Borang - hartini muchtar; Dianita Ekawati; Ali Harokan (STIKes Payung Negeri Pekanbaru, 2022)
Covid-19 is now a serious problem all over the world and the number of cases is increasing day by day. Attacking everyone, regardless of age or gender, is considered a pandemic. The global Covid-19 pandemic was first announced on March 11th, 2020. The Covid-19 vaccination aims to gain immunity in order to reduce the spread of the Covid-19 virus, reduce morbidity and mortality caused by Covid-19. This study aims to determine the analysis of the administration of Covid-19 vaccination in the elderly aged 60-75 years in the working area of ​​the Sematang Borang Health Center in 2022. This study was carried out on April 25-28 May 2022. This study was quantitative with a cross sectional design. The population of this research is people aged 60-75 years in the working area of ​​the Sematang Borang Health Center, totaling 320 samples, by using accidental sampling. Statistical test using chi square and logistic regression with a significance level (α = 0.05). The results showed that there was a relationship between education level (p = 0.032), history of comorbidities (p = 0.015), access to health services (p = 0.028), health information (p = 0.024), vaccine availability (p = 0.005), family support (p = 0.005), and family support (p = 0.005). p=0.054) and motivation (p=0.036) by giving Covid-19 vaccination. In the multivariate analysis, the dominant variable related to the administration of the Covid-19 vaccination was the availability of the vaccine (p=0.005; OR=0,498). It is recommended for the elderly to understand the importance of following the covid-19 vaccination, because the dose is well regulated to form the immune system.